Case-matched Comparison of Postoperative Outcomes Following Surgery for Inflammatory Bowel Disease After Exposure to Vedolizumab vs Other Biologics. (20th July 2019) - Novello, M; Stocchi, L; Steele, S R; Holubar, S D; Duraes, L C; Kessler, H; Shawki, S; Hull, L T
Abstract: Background and Aim: The effects of vedolizumab [VEDO] exposure on perioperative outcomes following surgery for inflammatory bowel disease [IBD] remain controversial. The aim of our study was to compare postoperative morbidity of IBD surgery following treatment with VEDO vs other biologics or no biologics. Methods: An institutional review board-approved, prospectively collected database was queried to identify all patients undergoing abdominal surgery for IBD between August 2012 and May 2017. The impact of VEDO within 12 weeks preoperatively on postoperative morbidity was initially assessed with univariate and multivariable analyses on all patients. A case-matched analysis was then carried out comparing patients exposed to VEDO vs other biologic agents, based on gender, age ± 5 years, diagnosis, date of surgery ± 2 years, and surgical procedure. Results: Out of 980 patients, 141 received VEDO. The majority of patients [59%] underwent surgery involving end or diverting ostomy creation. The initial multivariate analysis conducted on all patients indicated that VEDO use was independently associated with increased overall morbidity [ p <0.001], but not infectious morbidity [ p = 0.30]. However, the case-matched comparison of 95 VEDO-treated patients vs 95 patients treated with adalimumab or infliximab did not indicate any difference in overall morbidity [ p = 0.32], infectious complications [ p = 0.15], or surgical site infections [ p = 0.12]. Conclusions: In a study population having a high rate of surgery involving ostomy creation, the exposure to preoperative VEDO was not associated with an increased morbidity rate when compared with other biologics.